Implementası Kurıkulum Merdeka di Sekolah Dasar Tahun Ajaran 2022/2023 - Prabaningrum, Winanda Fajar; Sayekti, Ika Candra (Elementary Teacher Education Program, Majalengka University, 2023)
Curriculum change in Indonesia is one of the major changes in the world of education. Currently, the Kurikulum Merdeka is an option in the world of education, the objectives of this study are as follows 1) to describe the implementation plan for the independent learning curriculum, 2) to describe the independent learning curriculum learning plan, 3) to describe the implementation of learning based on the Implementation of Kurikulum Merdeka at SDN Pajang 1 Surakarta. This type of research uses a qualitative method, the research data is in the form of a curriculum applied at SDN Pajang 1 Surakarta. Retrieval of data using observation techniques, interviews, and documentation. The data validation technique uses the source triangulation technique, which is carried out by searching for data that is still related to utilizing various sources. Technical triangulation, namely obtaining data by using various techniques to be able to reveal data that is carried out to data sources. The conclusions from the results of the research are planning the implementation of the Kurikulum Merdeka at SDN Pajang 1 Surakarata which includes learning objectives, targets/achievements, compiling modules as teaching materials in accordance with the provisions and includes effective, interesting, essential, challenging, sustainable, relevant and sustainable components. Learning planning for the independent learning curriculum at SDN Pajang 1 Surakata is still not fully implemented according to the provisions of the Kurikulum Merdeka for the seven stages of learning planning. The implementation of Kurikulum Merdeka-based learning at SDN Pajang 1 Surakarta is well implemented and in accordance with the provisions of the Kurikulum Merdeka.